The magician's nephew - Lewis, C. S. (Clive Staples), 1898-1963 (Lewis, C. S. (Clive Staples), 1898-1963. Chronicles of Narnia, 2025)
Digory and Polly try to return the wicked witch Jadis to her own world, but the magic gets mixed up and they land in Narnia where they witness Aslan blessing the animals with human speech.